Mixed surfactant (altering chain length and head group) aggregates as an effective carrier for tuberculosis drug. (September 2018) - Kumar, Arun; Rekha,; Kansal, S.K.; Ibhadon, A.O.; Mehta, S.K.
Graphical abstract: Highlights: Mixed surfactant aggregates were prepared and characterized. Rifampicin solubilization was comparatively analyzed and improved. Rifampicin was stabilized in highly basic medium and in strong oxidizing condition. Interaction site of rifampicin within aggregates was evaluated. Abstract: Surface properties and aggregation behavior of cationic-cationic and cationic-non-ionic mixed surfactant systems viz. Dodecylethyldimethylammonium bromide (DDAB) with a series of double chain cationic surfactants (DiDDAB, DMDTAB, and DODAB) and non-ionic surfactants (Brij 96, Tyloxapol and Tween 80) were analysed using surface tension and transmission electron microscopy (TEM). The effect of chain length of cationic surfactant and hydrophilic-lypophilic balance (HLB) prominently observed in critical aggregation (cac) value. The aqueous solubility of anti-tuberculosis drug: rifampicin (RIF) was comparatively studied by UV–vis spectroscopy in presence of formulated micelles and vesicles. RIF was significantly solubilised in aqueous medium using all the formulated aggregates. RIF is very unstable in basic medium (above pH-7) and in oxidizing media. Therefore, stability at pH-13 as well as in strong oxidising environment was monitored using UV–vis spectroscopy. To trace the locus of the drug encapsulation in the micelles/vesicles, fluorescence spectroscopy and TEM studies were carried out. Both the techniques stemmed in complimentary results and confirmed that, RIF is majorly populated at polar medium in cationic-cationic vesicles and favour to reside at hydrophobic medium of the nonionic-cationic micelles.